70 let ljubiteljskega gledališča na Studencu - Sokler, Ajda (Amfiteater (Ljubljana), 2020)
In Slovenia, amateur cultural activities are strongly present. In the past, they had a particularly strong cohesive effect - "a combination of the pleasant and the useful". For many, especially those in rural areas, these activities were the only or most accessible option for spending their leisure time. In the 1930s, and after World War II, many amateur theatres formed, some later transformed into professional theatres, others reinforced their infrastructure and number of members. The latter is the case with the Studenec Summer Theatre established in 1949. Almost every summer since then, the Miran Jarc Cultural Society Škocjan stages its own theatrical productions. The first performance was under the local hayrack ( kozolec ), nowadays they are held in the modern covered theatre with approximately 1,000 seats. The drama group was originally brought together by a few local enthusiasts; the initiators of cultural creativity were the Stražar brothers. Today, the Studenec Summer Theatre combines local amateur and professional singers and actors. It stages its own productions; mostly light-hearted and accessible Slovenian plays and comedies with an aim to please the audience.
Keywords: Alojz Stražar; amateur theatre; Kulturno društvo Miran Jarc Škocjan; ljubiteljsko gledališče; Miran Jarc Škocjan Cultural Society; Poletno gledališče Studenec; rural; Stane Stražar; Studenec Summer Theatre